Memristores - Duarte, João Diogo Capela (2014)
The memristor was proposed by Leon Chua in 1971 only for the sake of mathematical complement, an idea that was not widely accepted by the scientific community. Only decades later, after HP’s announcement in 2008 is that the memristors started to be seen as realizable elements and not as mere mathematical curiosities. These devices feature distinct characteristics from the other known electronic devices. Besides being passive, they are characterized by the following postulates: the existence of a characteristic voltage-current loop with hysteresis and single valued in the origin, gradual decrease of the area defined by the loop with the increasing of the frequency and simply resistive behaviour for infinite frequency. As a memristive device’s response depends greatly on the amplitude and frequency characteristics of the input signal and its own internal characteristics. Therefore there is a clear need to find procedures and attributes that allow to classify and categorize various memristive devices. These attributes, in their essence, similar to the figures of merit of devices like diodes and transistors, will allow in the near future to better choose memristive devices for specific applications. To try to obtain these attributes, a morphologic analysis of the voltage-current loops’ area and length of several theoretical memristive devices models was made in MATLAB changing its internal characteristics, for arrays of frequency and amplitude values of the input signal. Afterwards, a memristor device emulator was built to corroborate the theoretical results obtained. To this end the voltage-current loops for several input values were measured and the calculation of the loops’ areas and lengths was effectuated.